(untitled) (Jurnal Kemanusiaan, 2019)
This paper primarily aims to develop a comprehensive model of initial trust by evaluating and integrating antecedents of interpersonal trust within the McKnight’s trust related models. We have firstly identified antecedents of interpersonal trustby reviewed the literature and subsequently classified them by evaluating the properties of the constructs. Based on the review, seven constructsrelated to antecedents of interpersonal trust have partly been identified toincorporatein and extend the McKnight’s trust models. They are: (1) situation normality, (2) structural assurance, (3) disposition to trust, (4) perceived site quality, (5) perceived vendor reputation, (6) co-brand image, (7) co-brand awareness. This study contributes academically by providing a comprehensive conceptual model, where these essential constructs are assembled together. Future empirical validation is suggested at the end of this paper.